Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/apm.12679
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic pathways of macrophages within osteolytic interface membrane in periprosthestic osteolysis after total hip replacement

Abstract: Macrophage apoptosis in interface membrane, which occurs through either death receptor, mitochondrion, or endoplasmic reticulum (ER) stress pathways, has been suggested to play an important role in promoting osteolysis. However, how and why macrophage apoptosis originates and the correlation among these apoptotic pathways is not yet clear. The objective of this study was to identify the apoptotic mechanism of macrophages, and to explore the relationship between the apoptotic pathways and progression of osteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Apoptosis is a tightly controlled process that was recognized inducing via three major ways, including mitochondrial, endoplasmic reticulum and death receptor signaling pathway [29]. The extrinsic death receptor-mediated apoptotic signaling pathway was investigated and apoptotic cascade related proteins involving TRADD/FADD, Caspase-3, caspase-7, PARP and their cleaved forms were all down-regulated in CRIP1 overexpressed CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a tightly controlled process that was recognized inducing via three major ways, including mitochondrial, endoplasmic reticulum and death receptor signaling pathway [29]. The extrinsic death receptor-mediated apoptotic signaling pathway was investigated and apoptotic cascade related proteins involving TRADD/FADD, Caspase-3, caspase-7, PARP and their cleaved forms were all down-regulated in CRIP1 overexpressed CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a human study investigating the effect of ER stress and apoptosis on osteolysis, ER stress and apoptosis were evaluated to cause loosening and loss of the prosthesis, and the apoptosis expression genes (BCL-2 and BAX) and ER stress markers (IRE1-α, GRP78 / Bip, CHOP, cleaved caspase-4, and JNK) expression levels were found to be signi cantly increased compared to the control group and there was a correlation between the degree of ER stress and the clinical severity of osteolysis. Thus, it was proven that ER stress exerts an impact on the apoptotic process in osteolysis [19]. Studies on human epithelial cells have investigated the role of ER stress in the development of epithelial-to-mesenchymal transition, in multiple tissues, including the eye, lungs, liver, and kidneys, and it has been revealed that ER stress triggers the development of epithelial-to-mesenchymal transition and causes pathological conditions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Ti particles stimulate the gathering of macrophages cells to produce a variety of proinflammatory cytokines, such as TNF-α and IL-6, in interfacial membranes [ 28 30 ]. In addition, the fibrous interface membrane around a loosening periprosthetic shows a predominance of macrophages, which represent 60–80% of the entire cellular population [ 31 ]. In the present study, our results also indicated that Ti particles increased the macrophage population, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%